PENGARUH HEALTH EDUCATION TENTANG STRATEGI PELAKSANAAN HALUSINASI PADA KELUARGA TERHADAP PERAN KELUARGA DALAM MEMBANTU KLIEN SCHIZOPHRENIA MENGONTROL HALUSINASI DI KOTA KEDIRI - Byba Melda Suhita; Intan Fazrin (STRADA : Jurnal Ilmiah Kesehatan, 2013)
Families need enough knowledge to help solve clients experiencing hallucinations nursing problems , one of which knowledge to assist the family members in helping clients control hallucinations . The purpose of this study to determine the effect of health education on hallucinations implementation familly strategic towards the family’s ability to help schizophrenia clients control hallucinations in Kediri. Research design in use One Group Pre – Test Post Test . Population family in Kediri with purposive sampling technique. Samples in this study were schizophrenia patients families in Kediri precisely at the Balowerti Public Health Centre and Sukorame Public Health Centre that meet the inclusion and exclusion criteria . Data collection is done by the questioner sheet , analysis of research data in the Mc Nemar test with α = 0.05 . The results showed that the role of the family in helping clients schizophrenic with hallucinations to controll hallucinations before being given health education, mostly in the active category , amount 8 respondents (66.75 %) and after being given health education have known that among the active role and passive half of the same number 6 respondents ( 50 % ) . The analysis showed no effect of health education on hallucinations implementation familly strategic towards the family’s ability to help schizophrenia clients control hallucinations in Kediri with p – value = 0.1. Health education is an continued process, provision of health education is only one conflict with the family’s experience in caring for schizophrenic patients and may reduce the role of the family , thus requiring continuous health education by health institutions up to the family to help schizophrenia clients control the hallucinations.